The Role of RGS Wonogiri ini Helping Improving Public Information Disclosure in Sendang Village - Mami Eva Novayani; Pawito; Agung Satyawan (Journal of Social Interactions and Humanities, 2022)
This article examines the role of Radio Giri Swara (RGS) Wonogiri in Helping to Increase Public Information Openness (KIP) in Sendang Village, Wonogiri District. Along with the promotion of public information disclosure, radio has a strategic role to contribute to its success. Moreover, for rural areas, radio is still an effective means of conveying various public information. The method in this research article is descriptive qualitative. The results of the study stated that there are several programs that support the increase in public information disclosure in Sendang Village, namely Teropong Desa and One Hour Together. The broadcast of this event publishes a lot of information that the public needs to know and can be accessed by the public.